Intellectual Rights Protection Law in the Technology Era: Academialogy Integrity Studies - Gunawan Widjaja (LEGAL BRIEF, 2022)
Technology and science advances have impacted all sectors of life, including business, health, and education. This development is not only related to business affairs because it has an impact on the law, especially the protection of Copyright or intellectual rights. This study will discuss copyright protection in academic philosophical works in an era where technology is developing very quickly, impacting the increasing prevalence of electronic plagiarism. To facilitate this discussion, our data search was carried out using a qualitative approach: collecting all data from literature sources related to books, published articles, and other data sources. After collecting the data, the next effort is to examine it to get relevant answers to discuss. The attempt to answer the problems of this study is by using a cultural study approach, analyzing data, interpreting data, and drawing conclusions that meet the requirements of valid data findings. Finally, this study concludes that the results include, among others, the state has prepared rules in the form of protection of intellectual property rights which are described as one of the most fundamental rights in which the government has a role in protecting in the form of legal assistance so that all copyright documents can be protected. With this legal protection, the state respects the efforts of a person's Copyright with economic value and prevents all forms of copyright infringement.